Artikel Review: Pengaruh Kecepatan dan Waktu Mixing Terhadap Karakteristik Fisik Tablet: Pengaruh Kecepatan dan Waktu Mixing Terhadap Karakteristik Fisik Tablet - Wulan Nurazzizah; Avissa Nabila Sungkar; Greuselda A E Bolla; Jenni Pradita Sari; Rizka Fitria Tsalatsa; Meylani Sutoro; Muhamad Reza Pahlevi (LP4M STIKes Karsa Husada Garut, 2026)
The mixing process is a critical stage in tablet manufacturing because it affects the homogeneity of the mixture and the final quality of the product. This study aims to determine the effect of varying mixing speed and mixing time on the physical properties of tablets, including hardness, friability, disintegration time, and weight uniformity. Powder formulations were evaluated at several levels of mixing speed and duration to observe the resulting changes in physical characteristics. The results showed that increasing the mixing speed and time can improve the homogeneity of the mixture, resulting in tablets with better hardness and weight uniformity. However, mixing conditions that are too high or too long can potentially cause over-mixing, which has an impact on quality degradation, such as increased friability or changes in disintegration time. Overall, an optimal combination of mixing speed and time is needed to achieve stable tablet quality and meet pharmacopoeial requirements. Keywords: Mixing, speed, blending, tablet quality, physical properties of tablets